The Structural Equation Modelling of First Level Health Facilities’ Performance-Based Capitation Payment in National Health Service - Aryani, Ari Dwi; Bachtiar, Adang; Candi, Cicilya (UI Scholars Hub, 2024)
The BPJS Healthcare Security implemented performance-based capitation/Kapitasi Berbasis Kinerja(KBK) payments to conduct structured and ongoingmonitoring of the First Level Health Facilities/Fasilitas Kesehatan Tingkat Pertama(FKTP)'s performance throughout Indonesia. This study aimed to examinethe direct and indirect effects of FKTP capacity on KBK and FKTP performance. This study was conducted in February 2023, and Structural EquationModelling analysis was performed with secondary data from the BPJS Healthcare Security system database in 2021. Human resources were defined as theavailability of doctors in FKTP, infrastructure as credentialing value, ownership and type of FKTP, and KBK, and performance as first contact, non-specialistoutpatient referral ratios, and Chronic Disease Management Program/Program Pengelolaan Penyakit Kronis(Prolanis) participant ratio. The analytical resultsrevealed that human resources directly and positively affected the KBK. The indirect effect analysis results suggested that only human resources impactedFKTP performance. In conclusion, human resources are critical in achieving the KBK and FKTP performance.